The impact of sudden stops in capital flows on output and investment: Selected emerging markets - EMARA, Noha; NI, Congcong; GAO, Ya (Turkish Economic Review, 2018)
Abstract. We evaluate how vulnerable the emerging markets are to sudden stops, that is, capital inflow reversals, using panel data for 12 emerging economies for the period 1976-2002 that experienced such reversals. We investigate the impact of sudden stops on the macroeconomic indicators of economic growth and investment by employing the Generalized Method of Moments (GMM) estimation methodology. A robustness check is performed using regional groups and introducing additional control variables. We find that sudden stops have lagging, negative, and robust effect on output and investment, while the effect on investment is not always robusth. Keywords. Sudden stops, Economic growth, Capital flows, Emerging markets, GMM. JEL. E40, F32, F36, G15.